ANTIBODY SCREENING EXAMINATION ON VOLUNTARY BLOOD DONORS AT BLOOD DONATION UNITS BANYUMAS REGENCY IN 2023 - ETIVIA, DEVI; Riadi, Ahmad; widodo, widodo; Lestari, Sri (Postgraduate Program , Poltekkes Kemenkes Semarang, 2024)
Blood donation is a humanitarian activity where someone donates blood voluntarily. Blood Donation Units are required to provide safe and quality blood products to avoid transfusion reactions. One effort that can be made is to carry out pre-transfusion examinations on donor blood, one of which is an antibody screening examination. The aim of the antibody screening examination is to detect the presence or absence of clinically significant irregular antibodies in both the patient and donor. The aim of this study was to determine the blood type, gender and age of antibody screening in voluntary blood donors at the Blood Donation Unit. This type of research is descriptive using observational methods which was carried out in March 2023 at the Banyumas Regency Blood Donation Unit. Samples were taken using a total sampling technique, namely all voluntary blood donors who underwent an antibody screening test. Data collection was carried out using the qwalist diagast tool and laboratory archives which were accessed via the SIMDONDAR system. The results of the antibody screening research from a total of 3198 voluntary blood donors showed that the highest results were in blood type O, namely 1236 (39%) donors, in men, namely 2196 (69%), and in the elderly (26).-60 years).namely 1531 (48%) donors